Information processing strategies and framing effects in developing country choice experiments: Results from rice farmers in India - Ortega, David L.; Ward, Patrick S. (Wiley, 2016)
This study explores the effect of various information processing strategies specifically related to attribute nonattendance in stated choice experiments. Our approach includes two forms of stated choice task nonattendance, each derived from separately framed questions asked immediately following the completion of each choice task. We also evaluate a measure of inferred serial nonattendance based on the posterior distributions of random coefficient estimates. We find that choice task nonattendance question framing statistically impacts marginal utility coefficients and, to a lesser degree, willingness‐to‐pay estimates. While direct questions addressing attribute attendance or nonattendance affect these estimates, inferred indicators of serial nonattendance suggest that many attributes are not likely ignored as often as respondents may indicate. Further research is needed to assess inferred versus stated approaches to modeling respondent information processing strategies.